Comparison of two active warming techniques on body temperature in healthy, anesthetized dogs premedicated with acepromazine or dexmedetomidine: A pilot study - Jacob P. Rastas; Qianqian Zhao; Rebecca A. Johnson (PLoS ONE, 2025)
Temperature regulation in dogs is significantly impaired during general anesthesia. Glabrous skin on paws may facilitate thermoregulation from this area and is a potential target for interventions attenuating hypothermia. This pilot study aimed to compare efficacy of an innovative warming device placed on the front paws (AVAcore; AVA), with no warming methods (NONE) and conventional truncal warming methods (CONV; circulating water blanket/forced air warmer) on rectal temperature and anesthetic recovery times. Dogs were premedicated with acepromazine (ACE) or dexmedetomidine (DEX), induced with intravenous propofol and maintained on isoflurane. The change in rectal temperature was statistically separated into three segments: 15 minutes following premedication, prior to induction (T0-T15), 15 minutes following anesthetic induction into isoflurane maintenance (T15-T30), and >30 minutes of isoflurane maintenance (>T30). Overall, when warming treatments and time points were combined, the decrease in rectal temperature from baseline was significantly greater with ACE than DEX (P < 0.05). When ACE and DEX were analyzed separately, changes in rectal temperatures did not differ between warming techniques at T0-T15 and T15-T30 (P > 0.05). However, at >T30 minutes, slopes of the temperature change differed between all three warming device groups, despite whether ACE or DEX was administered; temperature decreased least in CONV whereas the NONE had the largest decreases (P < 0.05). At >T30, when warming devices were considered separately, slopes of the temperature change in AVA and NONE did not differ between ACE and DEX (P > 0.050). However, in CONV, DEX had a significantly faster increase in slope than did ACE (P < 0.05). No differences in recovery times were observed between techniques or premedications (P > 0.05). Although CONV provided the most stable thermoregulation in anesthetized dogs, the AVAcore also moderated decreases in body temperature associated with general anesthesia despite premedication, providing an additional warming technique in dogs.